Novel Immunomodulators as Alternative to Antibiotic Therapy for Uterine Infection in Cattle and Buffalo - Kumar, Harendra (Indian Farming, 2015)
A study was made to find out about ideal therapies for uterine infection in cattle and buffalo. Based on several merits such as ease of availability, low cost, eco-friendly, least public health concern, better recovery and pregnancy in cattle and buffalo, the immunomodulators (E. coli LPS, autologous plasma, neem oil, garlic extract and colostral whey) are suggested as an alternative to antimicrobial therapy for uterine infection, which need experimentation on larger number of animals.